Harnessing Benson Relaxation Therapy to Stabilize Blood Glucose Levels in Elderly Diabetic Patients at Jember Nursing Home - Mukarromah, Siti Murdiyati; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2025)
Introduction: Diabetes mellitus is a metabolic disease characterized by increased blood glucose levels. This disease is often found in the elderly and elderly caused by degenerative processes. The use of Benson relaxation therapy as part of a comprehensive diabetes management program can improve the quality of life for diabetes sufferers. Aim: This case study aims to analyze the application of Benson relaxation to the problem of unstable blood glucose levels in Patient. Method: Elderly people with type 2 diabetes mellitus had their blood glucose levels measured levels during pre-intervention in the morning and post-intervention in the afternoon. Elderly people receive intervention twice a day for 20 minutes and continue for up to 6 days. Results: Elderly people with type 2 diabetes mellitus who were given Benson relaxation therapy experienced a decrease in blood glucose levels from before to after intervention from the first meeting to the fifth meeting. Conclusion: Implementation Benson relaxation therapy given to the elderly has an effect on reducing blood pressure glucose levels on results before and after intervention. Keywords: Diabetes Mellitus, Benson Relaxation Therapy, Elderly.